Analisis Nilai Budaya dan Religius dalam Cerita Rakyat Desa Pamotan sebagai Sumber Pendidikan Karakter - Iddha Aryani; Muhammad Dasri; Ika Kusumawati (Journal Prakarsa Paedagogia, 2025)
Folklore is an integral part of oral tradition that not only serves as entertainment but also embodies noble values that play an important role in shaping the character of society. In the educational context, folklore has great potential as a contextual learning resource because it contains moral, religious, social, and cultural messages that are relevant to students’ lives. This study aims to analyze the cultural and religious values contained in the folklore “Desa Pamotan” and to examine its implications as a source of character education in formal education. This research employs a qualitative approach using content analysis of the text of the folklore “Desa Pamotan” found in the book Cerita Rakyat Pesisir Timur Jawa Tengah. Data analysis was conducted through the stages of data reduction, data presentation, and systematic conclusion drawing to reveal the meanings and values embedded in the text. The findings indicate that the folklore “Desa Pamotan” contains moral values such as honesty, hard work, patience, and self-control; religious values such as prayer, belief in God, and spiritual practices; social values such as mutual cooperation, solidarity, and care for others; as well as cultural values including respect for nature, local traditions, and the origins of village toponymy. These values are highly relevant for integration into character education learning at the primary and secondary school levels. This study affirms that folklore can be utilized as an effective contextual learning resource for instilling character values while simultaneously strengthening cultural literacy and preserving local wisdom amid the challenges of globalization.